Fred Fenton Marathon Runner: The Great Race at Riverport School - Chapman, Allen (Salt Lake City, UT : Project Gutenberg, 2009)
"Fred Fenton Marathon Runner: The Great Race at Riverport School" by Allen Chapman is a children's adventure novel, likely written in the early 20th century. The narrative revolves around Fred Fenton and his group of friends, who are students at Riverport High School and are passionate about athletics, particularly leading up to a marathon competition. The story explores themes of friendship, competition, and the spirit of youth as Fred and his peers navigate adventures both in sports and in their encounters with rivals. At the start of the story, the boys engage in a spirited snowball contest, showcasing their camaraderie and competitive nature. Fred, who is an athletic star among them, impresses his friends with his throwing skills, which leads to a sudden and unexpected snowball fight with rival boys from Mechanicsburg. This lively introduction serves to not only introduce the characters and their dynamics but also sets the stage for the themes of competition and teamwork that will unfold as they prepare for the upcoming marathon. The opening also hints at various incidents to come, including adventures on the ice and the challenges posed by rival towns, adding layers to the plot as it progresses. (This is an automatically generated summary.)
Release date is 2009-09-26
Produced by Jim Ludwig
Keywords: Marathon running -- Juvenile fiction